The Use Of Acyclovir And Phyllanthusniruri Supplement as Medication For Recurrent Intraoral Herpes Infections - Marcia Marcia; Siti Aliyah Pradono (Journal of Dentistry Indonesia, 2012)
Recurrent intraoral herpes infection (RIH) is one of the recurrent herpes simplex virus type-1 infections (HSV-1). It presents as single or clustered painful ulcers occur mainly on the keratinized mucosa, with the size of one to five millimeter. The Onset of RIH is considered to be associated with various endogenous and exogenous triggers. Therefore, it is important to recognize each individual triggers to prevent and to minimize and the infection for recurring. This report will describe three cases of RIH associated with emotional and physical stress. All patients have experienced continous recurrence of the disease for almost a year. Symptoms included painful multiple minute ulcers on oral mucosa initiated with fever. Serology investigation on antibody against HSV-1 confirmed a reactive elevation in these patients. Treatment consisted of acyclovir per oral 1000 mg daily per oral, counseling on stress condition and intake of nutritional supplementation. Nevertheless, stress conditions were difficult to overcome, therefore long-term medications were recommended to prevent recurrence episodes. One patient was taken a long-term acyclovir therapy and the other two patients were taken long-term acyclovir therapy with Phyllanthusniruri (Meniran) supplementation. Follow-ups on three cases showed the benefit of taking Phyllanthusniruri (Meniran) supplementation as reduction in RIH symptoms, shorten healing time and prolonged recurrence interval. DOI: 10.14693/jdi.v17i2.47